Rereading the First Filipino interrogating Leon Ma. Guerrero's Rizal - Fernandez, Erwin S. (Iloilo City UP in the Visayas, 2009)
"This paper reexamined Leon Ma. Guerrero's prizewinning, The First Filipino, a biography of Jose Rizal published in 1963. The author traced the development of Guerrero as biographer beginning with his Ateneo years until he wrote his biography while fulfilling his job as ambassador to London. In this paper, the author reread his biography on Rizal with a detailed account of his life and his times. The paper also attempted to compare and contrast Gerrero's Rizal to other Rizals by contemporary Rizal biographers."
Keywords: Ma. Guerrero, Leon; Jose Rizal -- Biography